2014
DOI: 10.5796/electrochemistry.82.897
|View full text |Cite
|
Sign up to set email alerts
|

Direct Observation of Rate Determining Step for Nd2NiO4+^|^delta; SOFC Cathode Reaction by operando Electrochemical XAS

Abstract: The oxygen chemical potential of dense Nd 2 NiO 4+δ thin films on Zr 0.92 Y 0.08 O 1.96 electrolyte was investigated by operando X-ray absorption spectroscopy (XAS) measurements. Operando XAS at the Ni K-edge was measured under an applied voltage and various oxygen partial pressures at high temperature to simulate the operating conditions of solid oxide fuel cells (SOFCs). The absorption edge energy under various polarizations is similar to those measured under equivalent oxygen partial pressures under open ci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 21 publications
(19 reference statements)
1
5
0
Order By: Relevance
“…7721.65 eV) for the sample in the surface state, indicating the reduction of Co.Furthermore, this energy change was significant for the x = 0.4 sample (E 0 value of 7721.98 eV for the bulk state and 7721.21 eV for the surface state). This reduction of Co at the interface between the electrode and electrolyte was due to the charge compensation on the defected surface as observed in a previous study by our group 39. The results of the Co K-edge XAS of the surface and the bulk states of LaCoO 3−δ under applied potential are shown in Figure6a.…”
supporting
confidence: 78%
See 1 more Smart Citation
“…7721.65 eV) for the sample in the surface state, indicating the reduction of Co.Furthermore, this energy change was significant for the x = 0.4 sample (E 0 value of 7721.98 eV for the bulk state and 7721.21 eV for the surface state). This reduction of Co at the interface between the electrode and electrolyte was due to the charge compensation on the defected surface as observed in a previous study by our group 39. The results of the Co K-edge XAS of the surface and the bulk states of LaCoO 3−δ under applied potential are shown in Figure6a.…”
supporting
confidence: 78%
“…This active CoO x H y layer could promote the stability against Co dissolution and significantly improve the activity–stability factor, shedding light on disclosing the reaction mechanism of perovskite catalysts. The information on the electrode and electrolyte interface can be obtained by XAS using a film electrode. Total-reflection fluorescence XAS (TRF-XAS) , and depth-resolved XAS measurements of lithium-ion batteries and solid oxide fuel cells have been recorded to obtain surface-sensitive spectra. In particular, TRF-XAS, which integrates the fluorescence yield obtained under total reflection, investigates near electrode–electrolyte interfaces under operando conditions.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9][10] Although some studies successfully observed the physical/chemical states of electrodes and electrolytes, the reaction mechanisms could not be directly clarified because the applied analytical techniques required impractical experimental conditions (e.g., high-vacuum conditions) or provided only limited information. Recently, X-ray diffraction 11 and X-ray absorption techniques 12,13 have been used to analyze cathode reactions in high-temperature and high-voltage applications. When hard X-rays with energy of >5000 eV are used, the measurements do not require any specific experimental conditions, e.g., high vacuum and low temperature; thus, X-ray based techniques are considered to be suitable for in situ analysis of high-temperature electrochemical devices.…”
Section: Introductionmentioning
confidence: 99%
“…[16][17][18] The electronic and local structural changes of MIEC electrodes were analyzed from the 3d transition-metal K-edge in these studies. [16][17][18] The electronic and local structural changes of MIEC electrodes were analyzed from the 3d transition-metal K-edge in these studies.…”
Section: Introductionmentioning
confidence: 99%
“…Hard X-ray radiation is useful for operando observation because of its high permeability.For instance, the electrochemical reactiona tt he fuel cell electrode was studied by hard X-ray absorption spectroscopy. [16][17][18] The electronic and local structural changes of MIEC electrodes were analyzed from the 3d transition-metal K-edge in these studies. However,t he 3d transition-metal K-edge does not directly represent the electronic structure of the outermost orbitalo ft he electrode material, since the X-ray absorption spectra at the 3d transition-metal Kedge mainly observes the excitation of ac ore electron from the 1s to 4p orbital.…”
Section: Introductionmentioning
confidence: 99%